PENGARUH IMBALAN, PENGAWASAN, KONDISI KERJA, PENGEMBANGAN KARIER, PENGHARGAAN DAN KELOMPOK KERJA TERHADAP KEPUASAN KERJA PERAWAT PELAKSANA DI RUANG RAWAT INAP RUMAH SAKIT UMUM DAERAH TGK.CHIK DITIRO SIGLI - Tristi Yuanita (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2019)
Job satisfaction of nurses is an important aspect that needs to get the attention of the hospital in an effort to improve services to patients. If the job satisfaction of nurses are met, then the nurse will tend to have high motivation to work, otherwise if would lead to lower job satisfaction, absenteeism, strikes and other acts that harm the hospital. This study aims to examine the effect of compensation, supervision, working conditions, career development, rewards, and the working group on job satisfaction. This study used cross sectional design with quantitative approach in the General Hospital of TGK. Chik Ditiro Sigli in September and October 2015. The sample amounted to 57 nurses, using a questionnaire. Data analysis methods are univariate, bivariate and multivariate by using multiple linear regression. The results showed that in exchange, supervision, working conditions, rewards, working groups, no significant effect on job satisfaction. While the career development of a significant effect on job satisfaction. Influential variable is the most dominant career development. Suggested to the leadership of the hospital to provide an opportunity for nurses to improve education, allocation of funds for training, draw up a clear policy for the promotion and provision of equal opportunities to nurses for structural positions.